Determinants of Health Outcomes of Traumatic Brain Injury Patients at Meru Teaching and Referral Hospital - MUKINDU, FAITH KINYA (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Introduction: Traumatic brain injury is a disruption of the brain structure with its function caused by the application of an external source which is manifest as confusion, loss of consciousness, coma, or seizure. TBI is among the leading causes of admissions in hospitals globally and has been attributed to significant morbidity, mortality and disability. The objective of this study is to assess the determinants of health outcomes of patients with traumatic head injury seeking treatment at Meru teaching and Referral Hospital. Methods: A retrospective cross sectional design, will be used to conduct this study at Meru Teaching and Referral Hospital. The study population will be adult patients who have a diagnosis of traumatic head injury, seeking care and treatment at Meru teaching and referral hospital and health care workers managing patients at Accident and emergency department, adult surgical wards and critical care unit. A sample size of 84 patients will be the study participants. Data will be collected using a check list to collect primary data from patient’s files and questionnaires will be administered to health care workers to assess their level of knowledge on management of traumatic brain injury patient. Data collected will be entered into Statistical Package for Social Sciences (SPSS) version 24 and descriptive statistics used for analysis. Research findings will be presented in figures and tables. All ethical consideration will be observed by seeking ethical clearance from Meru University of Science and Technology (MUST) Institutional Research Ethics Review Committee MIRERC and a permit will be obtained from National Commission of Science and Technology and Innovation (NACOSTI). Informed consent will be sought from the study participants.